Legal Analysis of Support of Sexual Violence Against Children During the COVID-19 Pandemic - Rambu Hada Indah (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The impact of COVID-19 between 2018 and 2021 is not just on global issues, but also on the level of sexual offenses against children. Children are at risk due to a lack of parental control, an inhospitable atmosphere, and the advancement of science and technology as a source of fertile pornography. The goal of this research is to see if there's a link between the rise in sexual offenses against children during the COVID-19 outbreak and how to deal with the aftermath. This research approach is normatively carried out by creating scientific conclusions based on analyses of real data received from the government's official website and evaluating the legal impact or applicability of those findings. From 2018 through 2021, there was sexual violence.